FENOMENA LIVING AL-QUR’AN DALAM PERSPEKTIF NEAL ROBINSON, FARID ESACK DAN ABDULLAH SAEED - Tinggal Purwanto (MAWA IZH JURNAL DAKWAH DAN PENGEMBANGAN SOSIAL KEMANUSIAAN, 2016)
This paper explored the idea of Neal Robinson, Farid Esack and Abdullah Saeed in their books, Discovering The Qur'an: A Contemporary Approach To A Veiled Text, The Qur‟an: A User‟s Guide, and The Qur‟an: An Introduction in order to understand the living Qur‟an in moslem society. After reading these books, the writer found that the Qur‟an gave a strong presence in the lives of many Muslims. Various norms and practices concerning interaction with the Qur‟an have developed over time. Recitation of the Qur‟an was not only as Islamic artistic expression but also as a good reward. Memorizing al-Qur‟an is a demand and a need for many Muslims. In modern era, on one hand, the Qur‟an is always listened by electronic media, on the other hand, the Qur‟an was used as a protection from evil by wearing it as amulet. Ayahs of Qur‟an and certain surahs were believed that they have superiority and were recitated at specific times. Arabic calligraphy was considered one of the most important forms of Islamic artistic expressions. All in all,the Qur‟an was not only a guidance but also an ideology.